Deviasi Adat Melaik (Merarik) Suku Sasak Sebagai Norma Adat di Desa Penujak Dalam Persfektif Komunikasi - Saparudin Saparudin (Jurnal Dakwah dan Komunikasi, 2022)
This study focuses on the traditional merarik/melaik culture that is universally applicable in the Sasak tribe and is still being carried out, but it is still a matter of different perceptions. This study uses a qualitative method with techniques for obtaining data through interviews, observation and documentation. From the research that has been carried out, it is found that the traditional culture of merarik/melaik (escape) in the marriage customs of the Sasak tribe is not the actual Sasak custom but the actual marriage custom is belakok (promising). This is not the traditional marriage culture of the Sasak tribe of Lombok, but its appearance was initiated as a form of protest against the differences in social and economic strata. , Messages that need to be conveyed and Communicate (recipients of messages).